2006
DOI: 10.1158/1078-0432.ccr-05-2845
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Patient Selection for Gefitinib in Non–Small Cell Lung Cancer by Combined Analysis of Epidermal Growth Factor Receptor Mutation, K-ras Mutation, and Akt Phosphorylation

Abstract: Purpose: Mutations in epidermal growth factor receptor (EGFR) are strongly predictive of gefitinib efficacy in non^small-cell lung cancer. However, the presence of EGFR mutant nonresponses and nonmutant responses points out the need for more comprehensive analysis. Patients and Methods: For 69 non^small-cell lung cancer patients treated with gefitinib, we have extended our analysis to EGFR gene copy number by fluorescence in situ hybridization, mutations in K-ras, HER2, and exon 20 of EGFR by direct sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
140
1
5

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 229 publications
(154 citation statements)
references
References 34 publications
8
140
1
5
Order By: Relevance
“…Han et al (2006) recently reported that EGFR mutation and high gene copy number were associated with better objective response in univariate analysis. Only gefitinib-sensitive EGFR mutation was independently predictive of both response and survival in multivariate analysis.…”
Section: Egfr Mutationsmentioning
confidence: 99%
“…Han et al (2006) recently reported that EGFR mutation and high gene copy number were associated with better objective response in univariate analysis. Only gefitinib-sensitive EGFR mutation was independently predictive of both response and survival in multivariate analysis.…”
Section: Egfr Mutationsmentioning
confidence: 99%
“…One approach is to look at individual genes, especially those that are targeted by a given chemotherapeutic to better assess the probability a patient will respond to therapy (18)(19)(20)(21). Another approach is to use gene expression profiles, such as those derived by microarray analysis, to generate molecular signature sets that can also be used for patient selection during clinical trials and beyond (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be clear that activation of AKT via PI3K occurs through phosphorylation by phosphoinositide-dependent kinase-1 and/or phosphoinositide-dependent kinase-2 at serine and threonine residues (Ser 472/473 , Thr 308 ). Several authors reported that especially phosphorylation of AKT at Ser 473 is associated with resistance to chemotherapy/ radiotherapy (36)(37)(38)(39)(40), and it has been proposed that activated AKT promotes survival of cells exposed to ionizing radiation through inhibition of apoptosis (41,42) or enhancement of DNA double-strand break repair (31).…”
Section: Introductionmentioning
confidence: 99%